Improving the visibility and use of digital repositories through SEO - Arlitsch, Kenning (LITA guides., 2013)
Recent OCLC surveys show that less than 2 percent of library users begin their search on a library website, which is why search engine optimization (SEO) is so crucial. And though a survey of faculty researchers at four major universities showed that most consider Google and Google Scholar amazingly effective for their research, low Google Scholar indexing ratios for library institutional repositories is widespread because it ignores common library metadata. Arlitsch and OBrien, who have presented and published widely on the topic, show how to ensure that high-value content is visible to reseachers.